EVALUATION OF THE ADDED EFFECT OF AMRUTADI KASHAYA IN THE MANAGEMENT OF AMLAPITTA VIS A VIS ACID DYSPEPSIA - Chauhan Himanshu Raj*; Rajashekhar C.V (AYUSHDHARA, 2018)
In Ayurvedic text Mandagni is the main cause of all the Roga including Amlapitta. by the increased Drava guna and Amla guna of Pachaka Pitta affecting the Annavaha, Rasavaha, Raktavaha, Purishvaha srotasa; Samana, Prana, Apana Vayu; mainly Kledaka and partially Bodhaka Kapha. Prana vayu, which having the Karma of Aadana, help the Anna to enter in the Kostha where the Anna gets disintegrated by fluids and softened by unctuous substances. Samana Vayu stimulates the Jatharagni which is situated in Amashaya and as a result proper digestion process starts. Agni performs normal functions when food is consumed in appropriate time and with appropriate and serves as promoter of longevity. Describing the Samprapti of Amlapitta Acharya Charaka says that Aamvisha, when get mixed with Pitta, the disease Amlapitta develops whereas Acharya Kashyapa described that the disease is caused by vitiation of Doshas (Tridosha) causing Mandagni which leads to Vyadhi Amlapitta. Amlapitta can be correlated with Acid Reflux Syndrome which comprises of various types of Gastro-esophageal Reflux Diseases like Gastritis, Dyspepsia, Heartburn, Hyperacidity, Hypoacidity etc. Described in modern sciences. The conventional science tries to find a cure for this through PPI, Antacid therapy, etc. which often results in ill effects. Here comes the importance of herbal remedies of Ayurveda. Amrutadi kashaya show a wide range of therapeutic usages. Because of its properties like Ushanta, Tikshanta, Katu, Tikta rasa, Ushnaa veerya help in Samprapti vighatana of Amlapitta. when Amrutadi kashaya is used with Laghusutashekhara rasa then, its result increases many fold in Amlapitta. In this study 40 patients of Amlapitta were registered and 03 patient (6.66%) were got no improvement, 18 patients got mild -improvement, 19 patient were got moderate improvement, 0 patient got Marked improvement and complete cure.